Analisis Harga Pokok Penjualan Pada Pabrik Tahu Hidayah Di Kota Bengkulu - Tri Wahyu Ningsih; Wagini Wagini; Iswidana Utama Putra (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The purpose of this study was to analyze the cost of goods sold arising from the calculation of the cost of goods manufactured by the traditional system used by Hidayah tofu factory and the basis for calculating the cost of goods manufactured by the Activity Based Costing system that the researcher implemented.The type of research used in this research is quantitative descriptive research. Where the data was obtained from interviews with Hidayah tofu owners and then implemented using the traditional methods used by the factory and the Activity Based Costing method to determine the cost of good sold from the two methods.The results of the analysis using the traditional method of cost of good sold for fried tofu products is Rp. 283,300,000.00, which is lower than the Activity Based Costing method. Meanwhile, the cost of good sold for white tofu products is IDR 138,000,000.00, which is lower than the Activity Based Costing method. Whereas in the Activity Based Costing method the cost of good sold for fried tofu products is IDR 285,837,500.00 higher than the traditional method. Meanwhile, the cost of good sold for white tofu products is IDR 140,536,760.00 higher than the traditional method. This shows that calculations using the Activity Based Costing method are more accurate than traditional methods. Because in the Activity Based Costing method all costs incurred in production activities are included in the calculation component, namely the cost of depreciation of factory machine assets.